Stress management can facilitate weight loss in Greek overweight and obese women: a pilot study. (30th April 2013) - Christaki, E.; Kokkinos, A.; Costarelli, V.; Alexopoulos, E. C.; Chrousos, G. P.; Darviri, C.
Abstract: Background: Stress and negative emotions have been shown to be critical factors in inducing overeating as a form of maladaptive coping in obese people. Methods: The present study aimed to evaluate the efficacy of an 8‐week stress management programme that includes progressive muscle relaxation (PMR) and diaphragmatic breathing on weight loss and eating behaviour in a sample of overweight and obese women who started a weight‐loss programme. A total of 34 women with a mean (SD) body mass index of 38.17 (7.19) kg m − ² and mean (SD) age 47.35 (11.64) years were recruited from the outpatients Obesity Clinic of a public hospital in Athens. Participants were randomly assigned into a Stress Management (SM) and a control group. Anthropometric measurements were taken before and after the intervention, and the participants completed the following questionnaires: Dutch Eating Behaviour Questionnaire (DEBQ), Eating Attitudes Test (Eat‐26), Health Locus of Control (HLC) and Perceived Stress Scale (PSS) before and after the intervention. Results: The findings indicated a significant improvement in weight loss in the SM group [4.44 (0.83) kg] after intervention compared to the control group [1.38 (0.78) kg] ( P  < 0.05). A higher restrained eating behaviour was observed in the SM group after intervention compared to the control group, although there was no significant difference in perceived stress levels. Conclusions: The intervention group showed greater weight reduction, possibly because of the stress management programme, and a greater dietary restraint was demonstrated by them compared to the control group. It is likely that stress management could facilitate weight loss in obese women; however, more studies are needed to confirm this hypothesis.